(untitled) (Indian Journal of Nematology, 2024)
Entomopathogenic nematodes (EPN) and their symbiotic bacteria are well-known as biological control agents and are found to produce a wide range of bioactive secondary metabolites. Studies carried out at the Central Tuber Crops Research Institute (CTCRI) on entomopathogenic nematodes resulted in the identification of novel EPN belonging to Rhabditis (Oscheius) species. This study reports the purification of a nematicidal metabolite from the symbiotic bacterium associated with Rhabditis (Oscheius) species. The crude culture filtrate and ethyl acetate extracts of this nematode symbiotic bacterium showed significant nematicidal activity against Meleidogyne incognita. The bacterium was cultured in tryptic soy broth at 72 hours of incubation at 30°C. The ethyl acetate extract was purified by silica gel column chromatography and thin layer chromatography. HPLC combined with GC-MS and LCMS led to the identification of the major compound as Bis (2-ethyl hexyl) phthalate. Thus this nematode and the associated bacteria have the potential to be developed as nematicidal agent against plant parasitic nematodes.